2011
DOI: 10.1007/s10570-011-9509-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water interactions in cellulose suspensions on mass transfer and saccharification efficiency at high solids loadings

Abstract: Water is essential to the hydrolysis and conversion of lignocellulosic materials as it is both the medium through which enzymes diffuse to and products diffuse away from the reaction sites and a reactant in the hydrolysis reaction of the glycosidic bonds within the polysaccharides. However, little is known about how water interactions with the biomass change with solids content and how this affects mass transfer resistances during high solids saccharification. Nuclear magnetic resonance spectroscopy measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 44 publications
2
93
1
2
Order By: Relevance
“…In fact, a further increase in enzyme loading up to 250 or 300 FPU/g led to little further increase or even decrease in the sugar yield from the hydrolysis of these celluloses (data not shown). A possible reason may be that an increased enzyme loading results in increased medium viscosity, and the increased viscosity makes the diffusion of enzymes to the substrate and the leaving of products from the substrate vicinity more difficult, decreasing the efficiency of the hydrolysis reaction (Roberts et al 2011). As a whole, under an enzyme loading of 200 FPU/g, the hydrolysis reactions are no longer limited by enzyme availability so that the hydrolysis performance is truly determined by the structure of the cellulose materials.…”
Section: Yield Of Reducing Sugar During Enzymatic Hydrolysis Of Cellumentioning
confidence: 99%
“…In fact, a further increase in enzyme loading up to 250 or 300 FPU/g led to little further increase or even decrease in the sugar yield from the hydrolysis of these celluloses (data not shown). A possible reason may be that an increased enzyme loading results in increased medium viscosity, and the increased viscosity makes the diffusion of enzymes to the substrate and the leaving of products from the substrate vicinity more difficult, decreasing the efficiency of the hydrolysis reaction (Roberts et al 2011). As a whole, under an enzyme loading of 200 FPU/g, the hydrolysis reactions are no longer limited by enzyme availability so that the hydrolysis performance is truly determined by the structure of the cellulose materials.…”
Section: Yield Of Reducing Sugar During Enzymatic Hydrolysis Of Cellumentioning
confidence: 99%
“…It was also observed that order of magnitude differences in adsorption resulted in quantitatively similar differences in effective diffusivities. In addition, Roberts et al (2011) found that increasing solids content decreased the effective diffusion coefficients of proteins in bacterial cellulose substrates. This study will continue the work and discussions presented in Tozzi et al (2012) by using more substrates and a different diffusing molecule-in this case bovine serum albumin (BSA).…”
Section: Background Of Diffusion Concepts Usedmentioning
confidence: 98%
“…Solids content has been correlated with increases in yield stress and viscosity, and concomitant decreases in hydrolysis yields (Bennington et al 1990;Hodge et al 2008;Lavenson et al 2011a;Stickel et al 2009;Um and Hanley 2008). Diffusion rates in cellulosic fiber suspensions-specifically the time scales of diffusion of smaller molecules-have only been recently studied (Roberts et al 2011;Tozzi et al 2012;Wong and Reeve 1990). Diffusion in these high solids cellulose suspensions is poorly understood, especially diffusion rates of protein and enzyme molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus one possibility is that adding all the endo-acting enzymes at the beginning of the reaction gave more time for the full loading of endoglucanases to hydrolyze the substrate. Additionally, the longer exposure to the substrate added earlier in the reaction may allow for more release of constrained water, thus decreasing viscosities in the soluble phase and facilitating mass transfer of the same endoglucanases to biomass in subsequent additions (Roberts et al, 2011). The addition of new biomass to an ongoing biomass hydrolysis reaction (as in fed-batch mode) has been shown to adversely affect glucose yields (Rosgaard Fig.…”
Section: Timing Of Enzyme Addition Affects Liquefaction Ratesmentioning
confidence: 99%